Side Reactions in Aqueous Phase Polymerization of N‐Vinyl‐Pyrrolidone as Possible Source for Fouling. Issue 5 (13th August 2019) - Deglmann, Peter; Hellmund, Mario; Hungenberg, Klaus‐Dieter; Nieken, Ulrich; Schwede, Christian; Zander, Christian
Abstract: An improved kinetic model for the radical polymerization of N ‐vinyl‐pyrrolidone (NVP) in aqueous medium is developed. Quantum chemical simulations reveal that the transfer to polymer is of minor importance whereas the transfer to monomer by hydrogen abstraction in 3‐position of the pyrrolidone ring leads to a radical with a double bond which initiates a new chain bearing a terminal double bond (TDB). The resulting dead chains with one, two, or more TDB are the main source for a strong increase of molar mass in batch reactors at high conversion due to long chain branching and crosslinking. This can be a source for gel formation and fouling in continuous reactors. Abstract : An improved kinetic model for the radical polymerization of N ‐vinyl‐pyrrolidone in water is presented. Quantum chemical simulations reveal that transfer to monomer by hydrogen abstraction in 3‐position of the pyrrolidone ring leads to chains with terminal double bonds (TDB) and consequently to a strong increase of molar mass with conversion due to long chain branching and crosslinking.